Dinamika Pemahaman Konseptual Siswa dalam Pembelajaran Matematika Berbantuan Photomath - Aminullah Aminullah (FKIP Universitas Mataram, 2025)
Conceptual understanding is at the core of meaningful mathematics learning, as it helps students reason about relationships between ideas and apply mathematical principles logically. However, the learning process in the classroom still focuses heavily on procedural aspects, so that students tend to memorize solution steps without understanding their meaning. This study aims to analyze the dynamics of changes in students' conceptual understanding when using photomath in mathematics learning. The approach used is qualitative with an exploratory case study design, involving six 10th grade students at SMA Negeri 2 Dompu who have applied digital technology in learning. Data were obtained through observation, in-depth interviews, field notes, and documentation, then analyzed through data reduction, data presentation, conclusion drawing, and verification. The results showed that the development of students' conceptual understanding occurred through three main phases, namely algorithmic interpretation, conceptual reflection, and mathematical meaning integration. Photomath functions as a cognitive mediator that helps students transition from procedural thinking to a more reflective and deeper conceptual understanding. The effectiveness of this process is greatly influenced by the role of teachers in directing the use of technology to focus on meaning construction. This study confirms that technology-assisted mathematics learning can enrich conceptual understanding if it is designed to be reflective and oriented towards strengthening reasoning